Ischaemic postconditioning: cardiac protection after the event. (16th February 2015) - Jivraj, N.; Liew, F.; Marber, M.
Abstract Ischaemic heart disease remains the leading cause of death worldwide. Novel approaches to improve morbidity and mortality in this population are essential. Cardiac ischaemic postconditioning – the technique of applying alternating cycles of sublethal myocardial ischaemia and reperfusion after a sustained insult – is one cardioprotective strategy that can reduce reperfusion injury. Infarct size reduction and improvements in left ventricular ejection fraction have been demonstrated with mechanical or pharmacological postconditioning, both after spontaneous acute myocardial infarction, and associated with cardiac surgery. Nonetheless, the benefits of postconditioning can be easily attenuated. For maximal benefit, postconditioning demands a particular patient population (large area at risk, with little collateral blood flow), timely application and the measurement of appropriate clinical endpoints. Furthermore, confounders such age, sex and medication, as well as a plethora of co‐morbidities common in patients with ischaemic heart disease, all impact on the efficacy of postconditioning. This fragility requires the security of outcomes from large‐scale human trials to ensure robust applicability to everyday clinical practice, and to provide assurance of an impact on long‐term clinical outcome. This review highlights the development of current postconditioning algorithms, the findings from current proof‐of‐concept trials, and the barriers that may limit its broad uptake into clinical practice.